Pengaruh Komunikasi dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai pada Kantor Dinas Sosial Kota Depok - Yuni Triana; Andi Sopandi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the Influence of Communication and Physical Work Environment on Employee Performance at the Depok City Social Service. Both partially and simultaneously. The research method used in this study is quantitative research. The population used in this study is Depok City Social Service Employees. The sampling method used by the author in this study is the saturated sample method, where the sample is an employee of the Depok City Social Service. which amounted to 54 Employees. The data collection method used in this study is primary data. The primary data taken was the data on the answers from the respondents totaling 54 respondents. The results of this study show that Communication while working has a partial effect on the performance of employees at the Depok City Social Service Office which is evidenced by the tcal value of > ttable or (99.126 > 2.007) This is also strengthened by the value of Sig. < 0.05 or (0.026< 0.05). The Physical Work Environment also partially affects the performance of employees at the Depok City Social Service Office which is evidenced by the tcal value of > ttable or (10.092 > 2.007) This is also strengthened by the value of Sig. < 0.05 or (0.026 < 0.05). Communication and physical work environment have a simultaneous effect on employee performance at the Depok City Social Service Office as evidenced by the value of Fcal > Ftabel or (59.939 > 3.179), this is also strengthened by the value of Sig. < 0.05 or (0.026 < 0.05).